Spatial distribution and associated factors of female genital cutting among reproductive-age women in Ethiopia: Further analysis of EDHS 2016 - Ayenew Engida Yismaw; Zemenu Tadesse; Dereje Nibret Gessesse; Abebe Ayinalem Tarekegn; Yazachew Engida Yismaw (Elsevier, 2021)
Background: Female Genital cutting is one of the cultural rituals whose origin can be traced to ancient times. Female genital cutting is still highly prevalent in the developing countries in Asia and many areas Africa including Ethiopia. Determining the distribution of female genital cutting is vital to address the problem and therefore, the aim of this study is to assess Spatial distribution and associated factors of Female Genital Cutting among reproductive-age women in Ethiopia. Methods: This was a secondary data analysis of the Ethiopian demographic and health survey 2016. About 15,683 women in the reproductive age group were included in the study. Bernoulli model was used to investigate the presence of purely spatial clusters of female genital cutting using SaTScan™ software version 9.6. Both bivariable and multivariable logistic regressions analysis was conducted and the level of statistical significance was determined by a p-value of less than 0.05. Ordinary Kriging spatial interpolation method was used for predictions of female genital cutting in unobserved areas of Ethiopia. Results: The prevalence of female genital cutting in Ethiopia was 66.9% (95% CI 65.85%-67.93%). Being Muslim Religion follower (AOR = 2.17, 95% CI 1.79 to 2.53), Husbands being primary educated (AOR = 0.51, 95%CI 0.33 to 0.77), Residing in a rural area (AOR = 2.12, 95%CI 1.08 to 4.17), women being wealth index category middle (AOR = 1.55, 95%CI 1.12 to 2.14) and rich (AOR = 1.56, 95%CI 1.07 to 2.25), and being respondents age group of 20-34 (AOR = 1.77, 95%CI 1.10 to 2.85) and 35-49 (AOR = 2.44, 95%CI 1.46 to 4.08) were significantly associated with female genital cutting. Conclusion: Female genital cutting is found to be high. Increased Respondent's age group, being Muslim Religion follower, residing in a rural area, higher husband education, being in higher Wealth index, and residing in region other than Gambela and Tigray were contributing factors of female genital cutting in Ethiopia. Therefore, the effort shall be towards and promoting the husbands' education to decrease female genital cutting.